Soybean GH3 promoter contains multiple auxin-inducible elements. - Liu, Z B (1994)
The soybean GH3 gene is transcriptionally induced in a wide variety of tissues and organs within minutes after auxin application. To determine the sequence elements that confer auxin inducibility to the GH3 promoter, we used gel mobility shift assays, methylation interference, deletion analysis, linker scanning, site-directed mutagenesis, and gain-of-function analysis with a minimal cauliflower mosaic virus 35S promoter. We identified at least three sequence elements within the GH3 promoter that are auxin inducible and can function independently of one another. Two of these elements are found in a 76-bp fragment, and these consist of two independent 25- and 32-bp auxin-inducible elements. Both of these 25- and 32-bp auxin-inducible elements contain the sequence TGTCTC just upstream of an AATAAG. An additional auxin-inducible element was found upstream of the 76-bp auxin-inducible fragment; this can function independently of the 76-bp fragment. Two TGA-box or Hex-like elements (TGACGTAA and TGACGTGGC) in the promoter, which are strong binding sites for proteins in plant nuclear extracts, may also elevate the level of auxin inducibility of the GH3 promoter. The multiple auxin-inducible elements within the GH3 promoter contribute incrementally to the overall level of auxin induction observed with this promoter.